HERMENEUTICS OF THE WARIA: WARIA’S HERMENEUTICAL TAFSIR OF AL-FATIHAH - Fazlul Rahman (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
Qur’an, as it is believed by Muslims, is The Holy Book as well as the manifestation of The Words of God (Kalamullah). It has meanings which obviously was being ‘monopolized’ by The Ulama. In regarding of consequence, the authority of interpreting this Kalamullahseems ‘limited’ only for particular groups. Then, according the author it becomes the main factor leads the stagnancy of Quranic interpretation studies in this modern era. In this context, Schleiermacher’s teory about ‘psychological explication’ (1998), Paul Ricoeur’s theory about ‘distantiation and appropriation’ (1976), and ‘the marginalized reading of Scripture’ theory proposed by Simopoulos (2007), create a new path in interpreting Quran. From those theories, the author sheds the lights on hermeneutical interpretation of al-Fatihahby as one of the marginalized groups in Indonesia, the Waria. This paper concludes that the waria use their hermeneutical way of understanding the Scripture and produce not only anoriginal interpretation, but also contextual and full of theological reflections.